PRevention Intervention and Support in Mental health for people with aphasia (Aphasia PRISM): protocol and mixed methods analysis plan for two feasibility studies - C. Baker; M. L. Rose; D. Wong; B. Ryan; S. Thomas; D. Cadilhac; I. Kneebone (Discover Psychology)
Abstract Background People with aphasia commonly experience depression and anxiety. The individual therapy program, Aphasia PRevention Intervention and Support in Mental health (Aphasia PRISM) offers low intensity psychotherapeutic interventions using communication supports. Trained stroke clinicians from disciplines other than psychology (e.g., allied health professional, nurse, doctor) can deliver such interventions. The aim of the planned studies is to test the acceptability, feasibility and preliminary effectiveness of Aphasia PRISM for preventing depression and anxiety and supporting wellbeing in people with aphasia after stroke. Method This protocol describes two feasibility studies of the Aphasia PRISM using parallel, convergent, mixed methods designs. Participants will be adults with aphasia after stroke from a metropolitan healthcare site (Study A, pre-post case series, approximate n = 6) and two regional/rural sites (Study B, randomised controlled trial, n = 30; random allocation to either: treatment arm Aphasia PRISM + usual care; or attention control of secondary stroke prevention information + usual care) in Victoria, Australia. Eligible participants will be offered 7 weekly intervention sessions (via telehealth or in person). Other participant groups include stroke clinicians / site managers and family members. Feasibility will be assessed with treatment acceptability ratings (primary outcome) and secondary outcomes such as recruitment rate and participant clinical response. Participant clinical responses to intervention will be collected pre-intervention (baseline), concurrently (4 week acceptability measure), immediately post (8 weeks), follow-up (3 months) and follow-up at 6 months (Study B only). Descriptive statistics will be used to analyse quantitative data based on the type and distribution of data. Reflexive thematic analysis, an inductive approach will be used to analyse qualitative data. Discussion Aphasia PRISM offers the potential for trained stroke clinicians to deliver low intensity psychotherapeutic interventions with communication supports to people with aphasia. Studies A and B were registered with the Australian New Zealand Clinical Trials registry under one registration (ACTRN12620000209998) 20th February 2020.